HUBUNGAN PENERAPAN MANAJEMEN PUSKESMAS DAN KOMITMEN KERJA PETUGAS DENGAN MUTU PELAYANAN PENGOBATAN DI POLI UMUM PUSKESMAS KABUPATEN BANGKALAN (Studi di Puskesmas Se-Kabupaten Bangkalan) - ., Shobirin (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
Health care quality problems in health centers is growing into a serious public health problem . The low quality of puskesmas is often a complaint from the public . The demands of today's society will be quality health services is increasing. a strong commitment to be willing to devote all its capabilities for the benefit of health centers in improving the quality of health services. This research is analytic survey research with cross sectional approach with quantitative approach . Data collection at once at a time (point time approach) . The total sample of 105 doctors and nurses at the health center of Bangkalan Public Poli . To test the relationship pattern researchers used an analysis tool of logistic regression chi square test with SPSS version 16 . The results showed that: 1) with a p value of 0.001 No Relationship Management Application Service Quality Medical health center, 2) with p value 0.000 Labour Relations Officers Commitment to Quality Medical Care. Employees who have work commitments to be more responsible in providing the best service quality Keywords : Application management clinic, working Commitment , Quality of Service